Politik Hukum Pidana Dalam Penegakkan Undang-Undang Informasi Dan Transaksi Elektronik (ITE) - Endri Susanto; Hariadi Rahman; Nurazizah Nurazizah; Lisa Aisyah; Ema Puspitasari (Universitas Mataram, 2021)
Seeing the rapid development of technology in the digital world, relations between the global community cannot be limited, then the government needs to make a legislation to regulate the procedures and how to use social media properly, in order to protect the rights of other citizens as well. we are familiar with the ITE Law. This study aims to find out how the influence and role of legal politics in enforcing the ITE Law in Indonesia. The research method used is normative research, by analyzing Law number 19 of 2016 concerning Amendments to Law number 11 of 2008 concerning Information and Electronic Transactions. The results of the study indicate that in the enforcement of the ITE Law, legal politics has a large role because it is related to the existence of political will in the enforcement of the Aquo Law in which there is a very large structure related to legal politics.